In-Depth Analysis of the Peripheral Immune Profile of HER2+ Breast Cancer Patients on Neoadjuvant Treatment with Chemotherapy Plus Trastuzumab Plus Pertuzumab - Pesce Viglietti, Ayelén Ivana (2024)
Currently, therapy for early-stage human epidermal growth factor receptor 2-positive (HER2+) breast cancer (BC) is based on the combination of trastuzumab and pertuzumab plus chemotherapy in a neoadjuvant regimen. The INMUNOHER study aimed to detect immunological markers in peripheral blood and their association with treatment response. Sixty-two HER2+ BC patients were recruited. Pre-treatment samples were obtained before the start of treatment, while post-treatment samples were obtained after completing therapy and before surgery and were analyzed by flow cytometry. The pathologic complete response (pCR) rate achieved was 82.3%. The expression of the NKp30, PD-1, and TIM-3 receptors was reduced in the Natural Killer (NK)-CD56dim subset of patients who did not achieve pCR. Following therapy, many changes were found in leukocytes, including alterations in T cell lymphocyte proportions. Also, the percentage of NK cells decreased, and several phenotypic changes were observed in this population. After treatment, IFN-γ production by NK cells against HER2+-cells with or without trastuzumab was significantly reduced. HER2-targeted therapy plus chemotherapy demonstrated high efficacy in most patients, reducing the statistical power for finding immunological markers. However, NK subset phenotypes correlated better with response groups, and numerous changes in the percentage of leukocytes and T and NK cells, as well as changes in the functionality of NK cells, were observed in most patients after treatment, encouraging further research into these immune populations.